Caracterização de substâncias fenólicas e alcaloides dos resíduos do cupuaçu (Theobroma grandiflorum (willd. Ex spreng.) Schum) - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Theobroma grandiflorum is a species native of the Amazon with high economic potential, which belongs to the same genus as cocoa (Theobroma cacao). Its fruit, known as cupuaçu, is the largest in the genus Theobroma, reaching up to 4 kg in weight. The economic base of this species is concentrated in the mesocarp (pulp), widely known and commercialized for the production of juices, nectars, ice cream and others. In the process of obtaining the the cupuaçu pulp byproducts are generated which correspond to 65% by weight of each fruit, that although they are sources of phenolic substances and antioxidants are not used. This study aimed to describe the chemical composition of phenolic extracts and alcaloídicos of the epicarp and endocarp cupuaçu using chromatographic and spectrometric techniques. Different methods combined with ethanol and ethanol / water (7:3) was used for the extraction of phenolic substances and for extraction of purine alkaloids four specific methodologies for methylxanthines were used, in order to obtain the best conditions for extractions. The total phenolic content ranged between 8.62% (113.30 mgGAEs/g) and 12.96% (157.8 mgGAEs/g) for the epicarp extracts and between 3.17% (64.5 mgGAEs/g) and 12.86% (182.6 mgGAEs/g) for cupuaçu endocarp. The optimum conditions that provided the highest levels of phenolics and flavonoids were the extraction by maceration of the epicarp hot ethanol and the extraction of the endocarp by soxhlet ethanol / water (7:3). The profile of extractions obtained by mass spectrometry indicates the íons of the m/z 339, 325 e 311 characteristic of phenolic acids, as a major component both epicarp as the endocarp cupuaçu. The epicarp extracts showed better capacity scavenging free radicals (CI50=69,5 μg/mL) in relation to the endocarp (CI50=223,6 μg/mL). The presence of methylxanthines caffeine and teacrina were confirmed by mass spectrometry (MS) and high performance liquid chromatography (HPLC-UV) by comparison of the retention time of their respective standards. The confirmation of the teacrina molecule was performed by nuclear magnetic resonance (1 H NMR) and carbon (13 C NMR). The study of the utilization of these residues indicates the endocarp cupuaçu as excellent raw material source teacrina methylxanthine, addition to the unprecedented presence of caffeine and valuing both epicarp and the endocarp since they are considered byproducts of industrial pulps Amazon.
Keywords: Theobroma; Epicarpo; Endocarpo; Fenólicos; Metilxantinas; CLAE; Epicarp; Phenolic; Methylxanthine; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA